Deep Learning–Based Estimation of Implantable Collamer Lens Vault Using Optical Coherence Tomography - Assaf, Jad F.; Reinstein, Dan Z.; Zakka, Cyril; Arbelaez, Juan G.; Boufadel, Peter; Choufani, Mathieu; Archer, Timothy; Ibrahim, Perla; Awwad, Shady T. (American journal of ophthalmology, 2023)
To develop and validate a deep learning neural network for automated measurement of implantable collamer lens (ICL) vault using anterior segment optical coherence tomography (AS-OCT). Cross-sectional retrospective study. A total of 2647 AS-OCT scans were used from 139 eyes of 82 subjects who underwent ICL surgery in 3 different centers. Using transfer learning, a deep learning network was trained and validated for estimating the ICL vault on OCT. A trained operator separately reviewed all OCT scans and measured the central vault using a built-in caliper tool. The model was then separately tested on 191 scans. A Bland-Altman plot was constructed and the mean absolute percentage error (MAPE), mean absolute error (MAE), root mean squared error (RMSE), Pearson correlation coefficient (r), and determination coefficient (R2) were calculated to evaluate the strength and validity of the model. On the test set, the model achieved a MAPE of 3.42%, an MAE of 15.82 µm, a RMSE of 18.85 µm, a Pearson correlation coefficient r of +0.98 (P < .00001), and a coefficient of determination R2 of +0.96. There was no significant difference between the vaults of the test set labeled by the technician vs those estimated by the model: 478 ± 95 µm vs 475 ± 97 µm, respectively, P = .064). Using transfer learning, our deep learning neural network was able to accurately compute the ICL vault from AS-OCT scans, overcoming the limitations of an imbalanced data set and limited training data. Such an algorithm can assist the postoperative assessment in ICL surgery. •Deep learning neural network developed to automate measurement of ICL vault using AS-OCT.•Validated using 2647 scans from 139 eyes of 82 subjects from 3 different centers.•Model achieved a MAPE of 3.42%, MAE of 15.82 µm, RMSE of 18.85 µm, Pearson correlation coefficient r of +0.98, and coefficient of determination R2 of +0.96.•The model assists postoperative assessment in ICL surgery, reducing time and potential bias of manual measurements.